Vascular smooth muscle cell proliferation depends on caveolin-1-regulated polyamine uptake. Issue 6 (21st November 2014) - Grossi, Mario; Rippe, Catarina; Sathanoori, Ramasri; Swärd, Karl; Forte, Amalia; Erlinge, David; Persson, Lo; Hellstrand, Per; Nilsson, Bengt-Olof
Abstract : We demonstrate that caveolin-1 negatively regulates vascular smooth muscle cell polyamine uptake and show that caveolin-1-regulated polyamine uptake is critical for proliferative advantage of caveolin-1 deficient cells, providing proof-of-principle for targeting this mechanism as a strategy to fight unwanted proliferation. Abstract : Much evidence highlights the importance of polyamines for VSMC (vascular smooth muscle cell) proliferation and migration. Cav-1 (caveolin-1) was recently reported to regulate polyamine uptake in intestinal epithelial cells. The aim of the present study was to assess the importance of Cav-1 for VSMC polyamine uptake and its impact on cell proliferation and migration. Cav-1 KO (knockout) mouse aortic cells showed increased polyamine uptake and elevated proliferation and migration compared with WT (wild-type) cells. Both Cav-1 KO and WT cells expressed the smooth muscle differentiation markers SM22 and calponin. Cell-cycle phase distribution analysis revealed a higher proportion of Cav-1 KO than WT cells in the S phase. Cav-1 KO cells were hyper-proliferative in the presence but not in the absence of extracellular polyamines, and, moreover, supplementation with exogenous polyamines promoted proliferation in Cav-1 KO but not in WT cells. Expression of the solute carrier transporters Slc7a1 and Slc43a1 was higher in Cav-1 KO than in WT cells. ODC (ornithine decarboxylase) protein and mRNA expression as well as ODC activity were similar in Cav-1 KO and WT cells showing unaltered synthesis of polyamines in Cav-1 KO cells. Cav-1 was reduced in migrating cells in vitro and in carotid lesions in vivo . Our data show that Cav-1 negatively regulates VSMC polyamine uptake and that the proliferative advantage of Cav-1 KO cells is critically dependent on polyamine uptake. We provide proof-of-principle for targeting Cav-1-regulated polyamine uptake as a strategy to fight unwanted VSMC proliferation as observed in restenosis.